Influence of thyroid dysfunctions on pregnancy: a systematic analysis of evidence (Research, Society and Development, 2025)
Introduction: Prenatal care is essential for identifying thyroid disorders, such as hypothyroidism and hyperthyroidism, which can cause pregnancy complications. Selective screening is recommended, but it may lead to underdiagnosis of cases, while universal screening may improve maternal-fetal outcomes. Objective: To analyze the impact of prenatal screening for thyroid dysfunction on pregnancy outcomes in pregnant women. Method: Systematic review conducted from March to November 2024. The following inclusion criteria were adopted for study selection: primary studies published in the last decade, available in English and/or Portuguese, in the following databases: Virtual Health Library, PubMed/MEDLINE, SciELO, and Web of Science. After synthesis, the data were presented in tables containing the information necessary for the research objective. Results: The initial search identified 676 articles, and after selection and screening, eight studies remained for final inclusion. Hypothyroidism in pregnancy was associated with an increased risk of gestational hypertension, preeclampsia, eclampsia, preterm birth, and spontaneous abortion, especially with TSH > 4 mU/L. Treatment of hypothyroidism reduced these risks. Universal screening detected more cases than screening based on risk factors, showing the benefit of comprehensive screening programs. Conclusion: Studies indicate that universal screening for thyroid dysfunction in pregnancy can improve management and reduce complications, especially in cases of clinical hypothyroidism. However, the effects of subclinical hypothyroidism are less clear, and the effectiveness of treating mild conditions is questioned.